2021
DOI: 10.1177/0272684x211033460
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Anxiety and Stress Among Arsenic-Induced Cancer Patients in Indo-Gangetic Plains of Bihar: Role of Proactive Coping

Abstract: Arsenic induced cancer is a major public health issue in Indo-Gangetic plains of Bihar, India where 22 out of 38 districts report arsenic contamination of groundwater. Its psychological aspect is under studied in contrast to the physiological and social. This baseline correlational survey research explores the relationship and role of proactive coping on depression, anxiety and stress among this population. Depression, anxiety and stress were assessed in 77 consenting arsenic induced cancer patients with depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Rhizoma Gastrodiae, a major herbal medicine used in the clinical treatment of dizziness, vertigo, and other neurological disorders, has diverse pharmacological functions, including sedation, anti‐depression, anti‐anxiety, and anti‐oxidation 4,5 . To date, there have been many reports concerning anti‐depressive treatment with Rhizoma Gastrodiae, although its exact pharmacological basis and action target remain unclear 6,7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhizoma Gastrodiae, a major herbal medicine used in the clinical treatment of dizziness, vertigo, and other neurological disorders, has diverse pharmacological functions, including sedation, anti‐depression, anti‐anxiety, and anti‐oxidation 4,5 . To date, there have been many reports concerning anti‐depressive treatment with Rhizoma Gastrodiae, although its exact pharmacological basis and action target remain unclear 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…4,5 To date, there have been many reports concerning anti-depressive treatment with Rhizoma Gastrodiae, although its exact pharmacological basis and action target remain unclear. 6,7 It has been found that gastrodin (GAS), one of the important constituents in Rhizoma Gastrodiae, may inhibit depression through neuroprotective effect. 8 According to extant findings, brain neurons can be damaged by a variety of stressors, including neurotoxins, inflammation, and stress responses.…”
mentioning
confidence: 99%